Practical Test-Driven Development using C# 7 : Unleash the power of TDD by implementing real world examples under .NET environment and JavaScript. - Callaway, John.; Hunt, Clayton (Birmingham : Packt Publishing, 2018)
Test-Driven Development (TDD) is a methodology that helps you to write as little as code as possible to satisfy the software requirements, and that what you've written does what its supposed to do. If you're looking for a practical resource on Test-Driven Development this is the book for you. You've found a practical end to end guide that will ...
Creating a React applicationRunning the Create React App script; Mocha and Chai; Jest; Mocha; Chai; Sinon; Enzyme; Ejecting the React app; Configuring to use Mocha and Chai; A quick kata to check our test setup; The requirements; The execution; Starting the kata; Summary; Chapter 4: What to Know Before Getting Started; Untestable code; Dependency Injection; Static; Singleton; Global state; Abstracting third-party software; Test doubles; Mocking frameworks; The SOLID principles; The Single Responsibility Principle; The Open/Closed principle; The Liskov Substitution principle.
Print version record.
The Interface Segregation principle.
eBooks on EBSCOhost
Keywords: C; Microsoft .NET Framework; Application software -- Development; Logiciels d'application -- Développement.; Application software -- Development